A Cost-Benefit Analysis of Border Corruption in the Conflict Regions in Georgia and Moldova - Abashidze, Archil; Gvalia, Giorgi (European Scientific Journal, ESJ, 2020)
Corruption is perceived as one of the worst factors inhibiting the statebuilding process. It, however, poses a significant threat to young democracies. Some theorists argue that, under certain circumstances, corruption might bring some benefits that can even overweigh its costs. For example, minorities denied certain services that might profit from corruption by bribing their way through. This can contribute to lessening tensions between groups. This article examines two cases of frozen conflicts and the role corruption might have played in the conflict resolution process over the last decade: South Ossetia in Georgia and Transnistria in Moldova. After analyzing the "soft approach" of the Moldovan state and the "hard power" of the Georgian state towards corruption and smuggling on the borders with the secessionist regions, we argue that the costs young democracies pay for their unwillingness to combat corruption is significantly higher than the modest benefits they can derive from handling these challenges with caution 2 .